Strategi Bertahan Di Tengah Banyaknya Trend Coffee Shop Di Kota Palangka Raya: Studi Pada About Something Coffee Roastery - Dina Alfianurrahmah; Sri Rohaetin; Windy Utami Putri (Edunomics Journal, 2024)
The purpose of this study was to determine and analyze the survival strategy of the Coffee shop business at About Something Coffee amid the many trends of Coffee shops in Palangka Raya City. In this research, the Descriptive Qualitative method is used with data collection through semi structured interviews, observation and documentation. From the results of the research About Something Coffee has a strategy to survive by using niche market strategies (market nihce strategies) by retaining customers through distinctive characteristics such as taste, price and service. The SWOT analysis of About Something Coffee is divided into four parts, namely: a) strengths, namely good product quality, good drink taste, affordable prices, friendly and polite service, many variations of products sold and the atmosphere provided is comfortable. b) weaknesses, namely, raw materials that are difficult to obtain, a variety of flavors that are still lacking, pricing on the menu and there are spots that are easily sultry. c) Opportunities, namely, new innovations in products. d) Threats, namely the number of competitors/competitors and also the weather which is sometimes uncertain. Meanwhile, the TOWS matrix analysis obtained through the About Something Coffee SWOT analysis is divided into four parts, namely: a) Strength-opportunities strategy, which is to always innovate in accordance with the times. b) Strength-Threats strategy, which is to maintain service quality and provide services through the Go-Food and Grab Food applications. c) Weakness-Opportunities strategy, About Something Coffee makes competitors as motivation and uses the right promotional media to attract consumers. d) Weakness-Threats strategy, continue to develop innovations in order to compete and attract market share according to goals.